PENGARUH STRATEGI PEMASARAN RELASIONAL TERHADAP LOYALITAS KONSUMEN PADA (PPJK) PERUSAHAAN PENGURUS JASA KEPABEANAN PT. JASA MUTIARA SAMUDRA PEKANBARU - Yusriadi, Yusriadi (Sekolah Tinggi Ilmu Ekonomi Riau, 2018)
This research is meant to analyze and to test the influence of trustt, familiarity and professional awareness to the customer loyalty at PT. Jasa Mutiara Samudra. The sample collection technique has been done by using purposive sampling and the data analysis technique has been done by using multiple linear regressions and the samples are 31 corporate. The result of this research shows that trust and familiarity has negative and significant effect on customer loyalty. While professional awareness have positive and significant impact on customer loyalty. The suggestions in this study the company should be able to maintain and improve the implementation of relationship marketing on the dimension of professional awareness and make improvements in terms of relationship marketing strategies on dimensions of trust and familiarity